2
$\begingroup$

The case where you have to prove $(Q^{t}Q)_{ii} = 1 \ \forall \ 1 \le i \le n$ is simple (you can choose $e_{i}$ as your $x$) but I am not able to show that $(Q^{t}Q)_{ij} = 0 \ \forall \ 1 \le i, j \le n, \ i \neq j$. Any help will be appreciated.

$\endgroup$
2
$\begingroup$

Note that $$ \left\|Q\mathbf{x}\right\|=\left\|\mathbf{x}\right\|\iff\left\|Q\mathbf{x}\right\|^2=\left\|\mathbf{x}\right\|^2\iff\mathbf{x}^{\top}Q^{\top}Q\mathbf{x}=\mathbf{x}^{\top}\mathbf{x} $$ holds for all $\mathbf{x}\in\mathbb{R}^n$.

For one thing, take $\mathbf{x}=\mathbf{e}_j$, and the equality implies that $$ \mathbf{e}_j^{\top}Q^{\top}Q\mathbf{e}_j=\mathbf{e}_j^{\top}\mathbf{e}_j=1 $$ holds for all $j=1,2,\cdots,n$.

For another, take $\mathbf{x}=\mathbf{e}_j+\mathbf{e}_k$, and the equality implies that $$ \mathbf{e}_j^{\top}Q^{\top}Q\mathbf{e}_j+\mathbf{e}_j^{\top}Q^{\top}Q\mathbf{e}_k+\mathbf{e}_k^{\top}Q^{\top}Q\mathbf{e}_j+\mathbf{e}_k^{\top}Q^{\top}Q\mathbf{e}_k=\mathbf{e}_j^{\top}\mathbf{e}_j+\mathbf{e}_j^{\top}\mathbf{e}_k+\mathbf{e}_k^{\top}\mathbf{e}_j+\mathbf{e}_k^{\top}\mathbf{e}_k, $$ or using the last equality we just figured out, $$ 1+\mathbf{e}_j^{\top}Q^{\top}Q\mathbf{e}_k+\mathbf{e}_k^{\top}Q^{\top}Q\mathbf{e}_j+1=1+\mathbf{e}_j^{\top}\mathbf{e}_k+\mathbf{e}_k^{\top}\mathbf{e}_j+1. $$ This reduces to $$ \mathbf{e}_j^{\top}Q^{\top}Q\mathbf{e}_k+\mathbf{e}_k^{\top}Q^{\top}Q\mathbf{e}_j=\mathbf{e}_j^{\top}\mathbf{e}_k+\mathbf{e}_k^{\top}\mathbf{e}_j. $$ Note that $$ \mathbf{e}_j^{\top}\mathbf{e}_k\in\mathbb{R}\Longrightarrow\mathbf{e}_j^{\top}\mathbf{e}_k=\left(\mathbf{e}_j^{\top}\mathbf{e}_k\right)^{\top}=\mathbf{e}_k^{\top}\mathbf{e}_j, $$ and that, likewise, $$ \mathbf{e}_j^{\top}Q^{\top}Q\mathbf{e}_k=\mathbf{e}_k^{\top}Q^{\top}Q\mathbf{e}_j. $$ Consequently, we conclude that $$ \mathbf{e}_j^{\top}Q^{\top}Q\mathbf{e}_k=\mathbf{e}_j^{\top}\mathbf{e}_k $$ holds for all $j,k=1,2,\cdots,n$.

Finally, recall that $$ \mathbf{e}_j^{\top}A\mathbf{e}_k $$ returns exactly the $\left(j,k\right)$-th entry of the square matrix $A$. Thus $$ \left(j,k\right)\text{-th entry of }Q^{\top}Q=\mathbf{e}_j^{\top}\mathbf{e}_k=\delta_{jk}. $$

This immediately leads to $$ Q^{\top}Q=I_n\iff Q^{\top}=Q^{-1}. $$

$\endgroup$
1
$\begingroup$

\begin{align*} \left<Q^{\ast}Qx,x\right>&=\left<Qx,Qx\right>\\ &=\|Qx\|^{2}\\ &=\|x\|^{2}\\ &=\left<x,x\right>\\ &=\left<Ix,x\right>, \end{align*} so $Q^{\ast}Q=I$. Now use the fact that $\|Q^{\ast}x\|=\|x\|$ and conclude that $QQ^{\ast}=I$.

$\endgroup$
0
$\begingroup$

$(Qx)^TQx = x^TQ^TQx = x^Tx \ \forall x \rightarrow \ Q^TQ = I \rightarrow Q^{-1} = Q^T$ (the fact that $Q$ is invertible can be concluded from: $rank(Q^TQ) = rank(Q) = rank(I)$ )

$\endgroup$
0
$\begingroup$

If

$\Vert Qx \Vert = \Vert x \Vert, \tag 1$

then

$\langle Qx, Qx \rangle = \Vert Qx \Vert^2 = \Vert x \Vert^2 = \langle x, x \rangle; \tag 2$

thus,

$\langle x, Q^TQ x \rangle = \langle Qx, Qx \rangle = \langle x, x \rangle; \tag 3$

we are given that (1) holds for all $x$; hence so do (2) and (3). Now let for arbitrary vectors $y$ and $z$ let

$x = y + z; \tag 4$

then from (3),

$\langle y + z, Q^TQ(y + z) \rangle = \langle y + z, y + z \rangle; \tag 5$

we now have

$\langle y + z, Q^TQ(y + z) \rangle = \langle y, Q^TQ y \rangle + \langle y, Q^TQz \rangle + \langle z, Q^TQ y \rangle + \langle z, Q^TQ z \rangle, \tag 6$

and

$\langle y + z, y + z \rangle = \langle y, y \rangle + \langle y, z \rangle + \langle z, y \rangle + \langle z, z \rangle; \tag 7$

substituting (6) and (7) into (5) yields

$\langle y, Q^TQ y \rangle + \langle y, Q^TQz \rangle + \langle z, Q^TQ y \rangle + \langle z, Q^TQ z \rangle$ $= \langle y, y \rangle + \langle y, z \rangle + \langle z, y \rangle + \langle z, z \rangle, \tag 8$

whence, since (3) binds for all $x$,

$\langle y, Q^TQz \rangle + \langle z, Q^TQ y \rangle = \langle y, z \rangle + \langle z, y \rangle; \tag 9$

furthermore,

$\langle y, z \rangle = \langle z, y \rangle, \tag{10}$

and

$\langle y, Q^TQz \rangle = \langle Qy, Qz \rangle = \langle Q^TQy, z \rangle = \langle z, Q^TQy \rangle; \tag{11}$

(9) thus becomes

$2\langle z, Q^TQy \rangle = 2\langle z, y \rangle, \tag{12}$

or

$\langle z, Q^TQy \rangle = \langle z, y \rangle; \tag{13}$

since this holds for all $z$ we find

$Q^TQy = y = Iy \tag{14}$

for all $y$. Therefore

$Q^TQ = I, \tag{15}$

and from this we of course conclude that

$(Q^TQ)_{ii} = 1, \; 1 \le i \le n, \tag{16}$

and

$(Q^TQ)_{ij} = 0, \; 1 \le i, j \le n; \tag{17}$

finally, (15) directly yields

$Q^{-1} = Q^T. \tag{18}$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.